2021
DOI: 10.1088/1741-2552/abc7ef
|View full text |Cite
|
Sign up to set email alerts
|

Multi-dimensional persistent feature analysis identifies connectivity patterns of resting-state brain networks in Alzheimer’s disease

Abstract: Objective. The characterization of functional brain network is crucial to understanding the neural mechanisms associated with Alzheimer’s disease (AD) and mild cognitive impairment (MCI). Some studies have shown that graph theoretical analysis could reveal changes of the disease-related brain networks by thresholding edge weights. But the choice of threshold depends on ambiguous cognitive conditions, which leads to the lack of interpretability. Recently, persistent homology (PH) was proposed to record the pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
2
2
0
Order By: Relevance
“…Regarding the average Betti curves, the sample intercept for the B 0 curve showed an inverse sigmoid pattern that replicates previous findings in functional connectivity fMRI (Liang and Wang, 2017; Gracia-Tabuenca et al, 2020; Li et al, 2021) and PET (Lee et al, 2012) studies. Furthermore, the average B 0 curve of the randomized data reached the single component faster than the observed data, evincing a less segregated network.…”
Section: Discussionsupporting
confidence: 88%
“…Regarding the average Betti curves, the sample intercept for the B 0 curve showed an inverse sigmoid pattern that replicates previous findings in functional connectivity fMRI (Liang and Wang, 2017; Gracia-Tabuenca et al, 2020; Li et al, 2021) and PET (Lee et al, 2012) studies. Furthermore, the average B 0 curve of the randomized data reached the single component faster than the observed data, evincing a less segregated network.…”
Section: Discussionsupporting
confidence: 88%
“…Regarding the average Betti curves, the sample intercept for the B 0 curve showed an inverse sigmoid pattern that replicates previous findings in functional connectivity fMRI ( Liang and Wang, 2017 ; Gracia-Tabuenca et al, 2020 ; Li et al, 2021 ) and PET ( H. Lee et al, 2012 ) studies. Furthermore, the average B 0 curve of the randomized data reached the single component faster than the observed data, evincing a less distributed network.…”
Section: Discussionsupporting
confidence: 88%
“…In terms of the functional organization of the brain, previous cross-sectional studies have shown that the adolescent period is characterized by an increase in modularity and specialization ( Fair et al, 2009 ; Satterthwaite et al, 2013a ; Gu et al, 2015 ), with prominent effects in frontal and parietal systems, along with executive performance ( Marek et al, 2015 ; Gracia-Tabuenca et al, 2021 ). However, as far as we are concerned, TDA in human connectomes has mainly been applied to neuropsychiatric disorders ( H. Lee et al, 2012 , 2017 ; Gracia-Tabuenca et al, 2020 ; Li et al, 2021 ) but not to characterize the typical development. There is still a huge degree of incertitude in this field because of the great variability between samples, sexes, and cultures ( Sawyer et al, 2018 ), with special emphasis on the fact that some individuals have faster or slower pubertal development even when they have the same chronological age ( Blakemore et al, 2010 ; Vijayakumar et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Improvements within medical imaging have created new opportunities regarding both diagnosing and understanding many types of neurodegenerative diseases [8,9], one of which is AD. Since various neuroimaging technologies can differentiate neuropathological alterations, they have been widely used for AD diagnosis [10][11][12][13][14][15]. Fluorodeoxyglucose positron emission tomography (FDG-PET) imaging is one of the effective functional biomarkers for AD diagnosis by indicating glucose metabolism activity and distribution.…”
Section: Introductionmentioning
confidence: 99%